1969
DOI: 10.1113/jphysiol.1969.sp008904
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of salt and water absorption in the intestine of the eel (Anguilla anguilla) adapted to waters of various salinities

Abstract: SUMMARY1. The absorption of NaCi and water was studied by intraluminal in vivo perfusion of the intestine of the yellow European eel (Anguilla anguilla) adapted to fresh water (FW), to sea water (SW), and to double strength SW (DSW).2. The net lumen to plasma NaCl transport from diluted SW perfusion fluids was independent of the NaCl concentration in the Na+ concentration range tested. The NaCl absorption (expressed as ,t-equiv/100 g . hr.) increased from FW (mean +S.E.): Na+ 166+ 17, Cl-205+ 24 to SW: Na+ 363… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(43 citation statements)
references
References 30 publications
2
41
0
Order By: Relevance
“…Notably, the Cl -concentration of the absorbate increases with time of fasting, as would be predicted if there is a mechanism to control how much water flux follows ion flux through the transcellular pathway. Interestingly, the only other euryhaline teleost that is known to rely on intestinal rather than branchial Cl -uptake in freshwater is the eel (Kirsch, 1972;Grosell et al, 2000), and here too the concentration of the absorbate was higher in freshwater than in seawater animals (Skadhauge, 1969). Additional experiments (Skadhauge, 1969;Skadhauge, 1974) demonstrated that the intestinal water absorption in the eel was closely linked to, and presumably driven by, the active transport of Na + and Cl -, though the author suggested that this might occur via the lateral intercellular spaces (i.e.…”
Section: M Wood and M Grosell Peg Permeability And Water Flux Inmentioning
confidence: 99%
“…Notably, the Cl -concentration of the absorbate increases with time of fasting, as would be predicted if there is a mechanism to control how much water flux follows ion flux through the transcellular pathway. Interestingly, the only other euryhaline teleost that is known to rely on intestinal rather than branchial Cl -uptake in freshwater is the eel (Kirsch, 1972;Grosell et al, 2000), and here too the concentration of the absorbate was higher in freshwater than in seawater animals (Skadhauge, 1969). Additional experiments (Skadhauge, 1969;Skadhauge, 1974) demonstrated that the intestinal water absorption in the eel was closely linked to, and presumably driven by, the active transport of Na + and Cl -, though the author suggested that this might occur via the lateral intercellular spaces (i.e.…”
Section: M Wood and M Grosell Peg Permeability And Water Flux Inmentioning
confidence: 99%
“…Effects of salinity have been shown in eels, where the intestinal water absorption in seawater animals is far higher than in freshwater animals (Aoki et al, 2003;Kim et al, 2008;Skadhauge, 1969). At the molecular level, the water absorption mechanisms in the intestine of marine fish are driven by NaCl via an apical Na…”
Section: Introductionmentioning
confidence: 99%
“…To compensate for this, seawater teleosts drink copious volumes of water that are continually desalinated by the esophagus and gastrointestinal tract to produce a fluid that is roughly isotonic to blood plasma (17, 34). The constant absorption of ions, by the intestine, is critical as it lowers luminal osmolality and allows for solute-coupled water absorption, and, thereby, compensating for branchial water loss (45,46 (53), a process coupled to the ion transport mechanisms described above. The seawater teleost rectum also plays a role in water absorption.…”
mentioning
confidence: 99%